2020
DOI: 10.1186/s12929-020-00638-x
|View full text |Cite
|
Sign up to set email alerts
|

A novel c-Kit/phospho-prohibitin axis enhances ovarian cancer stemness and chemoresistance via Notch3—PBX1 and β-catenin—ABCG2 signaling

Abstract: Background: The underlying mechanism involved in ovarian cancer stemness and chemoresistance remains largely unknown. Here, we explored whether the regulation of c-Kit and plasma membrane prohibitin (PHB) affects ovarian cancer stemness and chemotherapy resistance.Methods: Mass spectrum analysis and an in vitro kinase assay were conducted to examine the phosphorylation of PHB at tyrosine 259 by c-Kit. The in vitro effects of c-Kit on membrane raft-PHB in ovarian cancer were determined using tissue microarray (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
1
21
0
3
Order By: Relevance
“…It ought to be noted that previous studies have demonstrated that PHB mediated the resistance to chemotherapy and BRAF -targeted therapy in tumor. 46 47 More than this, our study implicated that PHB also mediated the resistance to immunotherapy by transducing the signal from A20 to STAT3, suggesting PHB as a versatile regulator and a promising therapeutic target for the determination of the treatment outcomes of diverse therapeutic approaches in cancer.…”
Section: Discussionmentioning
confidence: 66%
“…It ought to be noted that previous studies have demonstrated that PHB mediated the resistance to chemotherapy and BRAF -targeted therapy in tumor. 46 47 More than this, our study implicated that PHB also mediated the resistance to immunotherapy by transducing the signal from A20 to STAT3, suggesting PHB as a versatile regulator and a promising therapeutic target for the determination of the treatment outcomes of diverse therapeutic approaches in cancer.…”
Section: Discussionmentioning
confidence: 66%
“…In OC, the zinc transporter ZIP4 was identified as a novel CSC marker that physically interacts with Notch3 and activates Notch3 signaling (Fan et al, 2020). Several studies also found that the activation of Notch3 signaling enhances CSC activity, especially in chemoresistant OC tumors (Kim et al, 2017b;Jeong et al, 2017;Fang et al, 2020), and the relevant mechanisms are discussed in Platinum and Taxane. Yuan et al (2015) In HCC, the activation of Notch3 signaling was found to inhibit Wnt/β-catenin signaling and increase the expression of the stemness-related protein Nanog, which promotes the maintenance of the CSC population, thereby contributing to the pathogenesis of HCC (Zhang et al, 2015).…”
Section: Notch3 and Cancer Stem Cell Propertiesmentioning
confidence: 99%
“…In OC, the zinc transporter ZIP4 was identified as a novel CSC marker that physically interacts with Notch3 and activates Notch3 signaling ( Fan et al, 2020 ). Several studies also found that the activation of Notch3 signaling enhances CSC activity, especially in chemoresistant OC tumors ( Kim et al, 2017b ; Jeong et al, 2017 ; Fang et al, 2020 ), and the relevant mechanisms are discussed in Platinum and Taxane .…”
Section: Notch3 and Cancer Stem Cell Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute myeloid leukemia (Abdollahpour-Alitappeh et al, 2018) Acute myeloid leukemia (Yabushita et al, 2018;Yan et al, 2019) -CD26 --Chronic myeloid leukemia (Herrmann et al, 2014) CD117/c-KIT Hepatocellular carcinoma (Xu et al, 2018) Ovarian cancer (Fang et al, 2020) Hepatocellular carcinoma (Xu et al, 2018)…”
Section: Cd123mentioning
confidence: 99%